Who pays for and who benefits from improved timber harvesting practices in the tropics?: lessons learned and information gaps - Applegate, G.; Putz, F.E.; Snook, Laura K. (Center for International Forestry Research, 2004)
Although reduced-impact logging (RIL) techniques are well known and generally endorsed by tropical foresters, rates of adoption of RIL by loggers have been less than encouraging. The principal impediment to proper planning of logging operations, training and supervision of forest workers, and the other components of RIL is apparently the belief on the part of loggers that these improvements are costly to implement. Although there are reasons to doubt that many forest managers and forest operators are fully aware of the costs of each component of their timber harvesting operations, it cannot be disputed that there are additional costs of implementing some aspects of RIL for some forest stakeholders over some time periods. It should therefore be useful to all parties concerned to disaggregate RIL into its components and to analyse the costs and benefits of each from different perspectives. For example, if timber harvesting companies only obtain a portion of the benefits of RIL, then from their perspective it may not be appropriate to pay all of the supplementary costs associated with implementing RIL practices. To explore this issue in detail, this paper analyses four components of improved timber harvesting practices (stock and topographic mapping, directional felling, road planning and construction, and skid trail and road closure) on the basis of who pays the costs of implementation and who derives the benefits over both short and long terms. It is hoped that the information generated will assist in efforts at identifying which improved timber harvesting practices may require incentives and which can reasonably be considered the intrinsic responsibility of the timber harvesting company or contractor.